An Impact of Graded Surveillance Measure (GSM) on Financial Performance of Selected Indian Listed Pharmaceutical Companies - Dr. Umesh S. Rabari (International Journal of Engineering and Management Research, 2023)
During last few years many scams have come out in our country that leads to adverse impact on the interest of stakeholders who invest their hard-earned money in the companies. The faith of the investors reduces and they may switch over to some protected or closely control investment avenue or they may not invest at all due to unethical practices. This may lead to adverse impact on economic growth of the country. To avoid this consequences, Graded Surveillance Measure (GSM) is implemented as one of the measure of investors’ protection. The aim of Graded Surveillance Measure (GSM) is to advise and alert investors to be more cautious while dealing in shortlisted securities. The main objective of the study is to analyse an Impact of Graded Surveillance Measure (GSM) on Financial Performance of Selected Indian Listed Pharmaceutical Companies. The researcher has analysed collected data of selected companies to understand the impact of Graded Surveillance Measure (GSM) on Financial Performance of Selected Indian Listed Pharmaceutical Companies.